Students' Self-Reflection in their Grammar Learning at English Department of UNP - Maulana, Ivan; Rani, Yati Aisya (Universitas Negeri Padang, 2025)
This study aims to describe students’ self-reflection practices in grammar learning among students of the English Language Education Study Program at Universitas Negeri Padang (UNP). The main focus of the research includes the forms of self-reflection employed by students, their perceptions of its importance, and the challenges they encounter in applying self-reflection throughout the grammar learning process. A qualitative descriptive approach was used, with data collected through in-depth interviews. The interview questions were based on seven key indicators of self-reflection: journaling, talking with peers, practicing mindfulness, engaging in creative expression, spending time alone, attending counselling, and speaking or podcasting. The population of this study consisted of students who had completed all grammar courses in the English Education Program at UNP. The findings indicate that most students engage in self-reflection as part of their learning routine, either through written journals or personal contemplation. Students acknowledge that self-reflection aids in recognizing their weaknesses, correcting errors, and deepening their understanding of grammar. However, several challenges were identified, including a lack of guidance from lecturers, time constraints, and low levels of self-awareness among some students. These findings emphasize the vital role of self-reflection in enhancing the effectiveness of grammar learning and point to the need for institutional support to systematically incorporate reflective practices into the learning process.